In-vitro evaluation of marginal adaptation of crown restorations fabricated from different hybrid ceramic materials - Şaar, Emced (My University, 2019)
Amaç: Bu çalışmanın amacı, iki farklı hibrit CADCAM seramik materyal (CERASMART, VITA ENAMIC) ve bir lityum disilikat CADCAM seramik materyalden (IPS E.max CAD) üretilen kron restorasyonların marjinal adaptasyonunu silikon replica tekniği kullanarak değerlendirmek ve karşılaştırmaktır.Gereç ve Yöntemler: Çekilen 45 molar diş her grupta 15 örnek (n = 15) olarak rastgele 3 gruba ayrıldı. Test örnekler CAD/ CAM tekniği kullanarak üç farklı materyaldan üretildi. A grubu (CERASMART), B grubu (VITA ENAMIC), C grubu (IPS E maxs CAD). Her diş oto polimerize akrilik rezin bloklarına yerleştirildi. Tüm dişler standart diş preparasyon işlemlerine uygun olarak chamfer marjin dizaynına göre hazırlandı. CAD/ CAM sistemi (CEREC Omnicam Sistemi, Salzburg, Österreich) ile dijital ölçümler alındı. Restorasyonların marjinal adaptasyonu silikon replika tekniği ölçüldü. Toplanan veriler, (SPSS) kullanılarak analiz edildi.Bulgular: Marjinal, iç marjin, aksiyel, ve okluzal bölgelerde tüm gruplar arasındaki fark istatistiksel olarak anlamlı değildi P <0,05. En küçük ortalama değer Emax grubun marjininde (74.102 μm), en büyük ortalama değer ise Vita Enamic grubunun okluzal bölgesinde (94.281683 μm) tespit edildi.Sonuç: Bu in vitro çalışmanın sınırlılığı dahilinde: her üç materyalin marjinal adaptasyonu klinik olarak kabul edilebilir sınırlardadır.

Aim: Hybrid ceramics are new materials that combine the favorable properties of ceramics and composites. The aim was to evaluate and compare the marginal adaptation of crown restorations fabricated from two different hybrid CADCAM ceramic materials (CERASMART, VITA ENAMIC) and a lithium disilicate CADCAM ceramic material (IPS E.max CAD) using silicone replica technique. Materials and Methods: 45 extracted molar teeth were divided into 3 groups randomly, each group containing 15 specimens (n=15). Test specimens were fabricated with CAD/ CAM technique using three different materials. Group A (CERASMART), group B (VITA ENAMIC), group C (IPS e Max CAD). Each extracted tooth was placed in auto polymerizing acrylic resin blocks. All the teeth were prepared according to standard tooth preparation procedures with a chamfer finish line. Digital impressions were taken with CAD/ CAM system (CEREC Omnicam System, Salzburg, Österreich). The marginal Adaptation of the restorations was measured with silicone replica technique. The collected data were analyzed using the Statistical Package of the Social Sciences (SPSS) program. Results: The differences between all the groups in the marginal, internal margin, axial, occlusal areas were statistically insignificant P< 0,05. The smallest mean value was found in the margin of the Emax group (74.102 μm), and the largest mean value was found in the occlusal area of the Vita enamic group (94.281683 μm). Conclusion: within the limitation of this in-vitro study: the marginal adaptation of all three materials is considered clinically acceptable.
Keywords: CADCAM; Diş; Health; Hibrit seramik; Hybrid ceramics; Marginal adaptation; Marjinal uyum; Sağlık; Tooth